2023
DOI: 10.1088/1402-4896/acf350
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and corrosion characteristics of micro-arc oxidized magnesium alloy (ZE41) friction stir welds in modified SBF

N Sivashanmugam,
KL Harikrishna,
S R Koteswara Rao
et al.

Abstract: Magnesium is a popularly known class of biodegradable metallic biomaterials, and it has spent most of its time in corrosion environments that must be validated before it can be used in real bio applications. This work studies the adaptability of rare earth magnesium alloy (Mg-RE) ZE41 welds for in vitro bio applications. Magnesium rare earth ZE41 alloy plates were welded through a friction stir joining process. The fabrication of a defect-free and strong friction stir butt joint was confirmed by microscopic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…It was found that the weld samples exhibited lower yield and tensile strengths as compared to the base material samples. The variation in tensile strengths was attributed to the inclusion of different phases of non-homogeneity in the structure because of plastic deformation [34]. During tensile tests, tensile failures occurred in the heat-affected zone (HAZ) of the weld samples, and similar trends were reported in related studies.…”
Section: Mechanical and Microstructural Properties Of Zm21 And Ze41 M...supporting
confidence: 70%
See 1 more Smart Citation
“…It was found that the weld samples exhibited lower yield and tensile strengths as compared to the base material samples. The variation in tensile strengths was attributed to the inclusion of different phases of non-homogeneity in the structure because of plastic deformation [34]. During tensile tests, tensile failures occurred in the heat-affected zone (HAZ) of the weld samples, and similar trends were reported in related studies.…”
Section: Mechanical and Microstructural Properties Of Zm21 And Ze41 M...supporting
confidence: 70%
“…Furthermore, it can be deduced from the EIS studies that the SZ of the FSW joint displayed better corrosion resistance properties compared to the corrosion resistance of the base metal in both the untreated and MAO-treated conditions. The enhanced corrosion resistance of the stir zone (SZ) is attributed to the rapid and easier development of a stable passive layer [34], a direct consequence of the microstructural transformations induced by the friction stir welding (FSW) process.…”
Section: Electrochemical Impedance Spectroscopy (Eis) Studies Of Zm21...mentioning
confidence: 99%
“…Nonetheless, these procedures can be expensive and timeconsuming. Coatings, such as anodizing and plasma electrolytic oxidation, can provide excellent corrosion resistance but can be prone to delamination and cracking [38,39]. Hence, the choice of method depends on the specific application and performance requirements.…”
Section: Corrosion Resistance Improvementmentioning
confidence: 99%
“…Specifically use of ZrB 2 particles as reinforcement has always enhanced the mechanical properties of MMCs [17,18]. To achieve this, a carefully designed set of welding parameters is employed during the FSW process [19,20]. The study encompassed an examination of essential mechanical features, such as ultimate tensile strength, yield strength, hardness, and corrosion tests.…”
Section: Introductionmentioning
confidence: 99%